Importance and Effectiveness of the Adventist Educative Philosophy in Chile - León, Vicente (2012)
In Adventist school and secondary school of Chile was done a study in order to know the opinionof the secondary 4th grade and basic 8th grade students about the importance that thoseassign to the foundations of the Adventist Educative Philosophy. In these student groups wereobserved how much of the education philosophical objectives have been achieved. Furthermore,an analysis was accomplished to determine if exist a meaningful difference between theimportance and the achievement of the spiritual and academic social dimension and if thesewere affected by their religious affiliation. Research was performed in 35 primary schools and20 secondary schools during 2011 school period. In this study participated 2,257 studentsdivided in two groups: 824 of secondary’s students, and 1433 of primary‘s students. Theseresults have showed that there is a meaningful difference between the importance and theobjectives achievement regarding to the Adventist educative philosophy. On the other hand,among secondary fourth grade students who are Adventists and others that do not belongto any religion have showed less satisfaction regarding to the objectives achievement of theAdventist educative philosophy than another group of catholic students of the same grade,while basic 8th grade students have showed satisfaction with the objectives achievement. Asa result, three relevant aspects of the Adventist educative philosophy seem having lost theexpectation in students who have participated in this study such as: that these schools maypossess Adventist teachers, that students can develop abilities for the gospel preaching, andthat students can witness of their faithful to others.